Two-phase flow simulation with lattice Boltzmann method - Che Sidik, Nor Azwadi; Takahiko, Tanahashi (Faculty of Mechanical Engineering, UTM, 2007)
This paper concerned with the simulation of two phase fluid flows in two dimensions using lattice Boltzmann method. The original free energy lattice Boltzmann model is reviewed in some detail. Which was then developed into a new free energy model based on the isotropy approach and The Gallilean invariance is also considered. Some simulation results, which have been performed elsewhere, are repeated to test the validity of this model